Hemodialysis-induced renal perfusion decline: unraveling the pathophysiological mechanisms linking intradialytic circulatory stress to residual renal function loss - Xie, Dayang; Tan, Jiaming; Zhang, Qingtao; Yu, Qian; Wang, Yiqin; Wang, Yujin; Gao, Li; Yan, Liyuan; Zhou, Jianhui; Li, Nan; Cai, Guangyan (Frontiers in Pharmacology, 2025)
BackgroundResidual renal function (RRF) plays a critical role in quality of life and survival in hemodialysis (HD) patients but characteristically declines after the initiation of HD. Owing to incomplete understanding of the pathophysiology underlying RRF decline, protective strategies remain limited. The aim of this study was to explore the dynamic changes of renal perfusion in incident HD patients with preserved RRF during dialysis sessions and to provide new strategies for RRF preservation.MethodsThis prospective cohort study enrolled 30 incident HD patients with preserved RRF. Renal perfusion was serially assessed using contrast-enhanced ultrasonography (CEUS) at three time points during the HD session: pre-dialysis baseline, intradialytic phase (3 h post-initiation), and post-dialysis recovery phase (15 min after session completion). Renal perfusion was quantified using the CEUS-assessed perfusion index (PI). The primary outcome measure was the PI.ResultsDuring hemodialysis sessions, the PI as a surrogate marker of renal perfusion decreased by 17.53% (P < 0.001), which exhibited a negative correlation with ultrafiltration (UF) rates (Spearman’s r = −0.770, P < 0.001), but not with other variables such as sex, age, body mass index (BMI), blood pressure (BP), estimated glomerular filtration rate (eGFR), hemoglobin, or albumin levels.ConclusionThis study demonstrates that incident HD patients experience an acute decrease in renal perfusion during hemodialysis, which is negatively correlated with mean UF rates. This finding may represent a crucial step toward elucidating the pathophysiology of hemodialysis-mediated RRF decline.Clinical trial registrationclinicaltrials.gov, identifier (NCT07003828).